Pancasila Student' Profile Project in Overcoming Characters Decadency in The Disruption Era - Mindani, Mindani; Asvio, Nova; Yumarni , Asmara (Islam Transformatif : Journal of Islamic Studies, 2024)
Pancasila Student Profile Strengthening Project, known as P5, is a new solution to build valuable students' characters. This study analyzes how P5 was implemented in schools to conquer character decadency in the disruptive era. This study used a qualitative research design to collect the data and a triangulation test to validate the data. The research data was collected in three elementary schools in Bengkulu City. The findings indicate that P5 is running well at the sample schools by looking at several indicators, such as the policy, program, and implementation of P5. Based on the data, the schools accepted and implemented P5 to swamped character decadence in the period of disruption well, allowing it to be socialized and applied as needed. However, every school has successfully utilized P5 techniques to overthrow character decadence in the disruptive era. Despite the challenges and limitations associated with its implementation, the principal has the ability to mitigate these issues. The principal and educators hope the school can best apply P5 to combating character decadence in the disruptive period, making it more advantageous for the larger community.